ADVANCEMENT OF ISLAMIC BANKING AND FINANCE IN THE SOCIO-ECONOMIC CONTEXT OF BANGLADESH BASED ON IBBL - Ahmad, Faisal (International Journal of Islamic Banking and Finance Research, 2022)
This study's background is in the context of comparative activities and achievements highlighted by Islami Bank Bangladesh Limited in their Annual Report 2020. The purpose of this study is to present the socio-economic impact and role of Islamic banks in the economic development of Bangladesh. This research has tried to prove how Islami Bank contributes through various tests and methods. Comprehensive profile analysis was conducted by collecting data using a Google survey form from a sample of 100 Islamic bank customers. Firstly, based on the respondents' responses, most of the customers of Islamic banks are between 25-40 years based on age. First, the customers are highly educated and have a stable relationship with the bank. Second, awareness of clients and the current use of deposit instruments is commendable. Third, customers in education and income classes have an important role in using various banking services or products. Fourth, customers are always satisfied with using various products and services. Fifth, within the service delivery system, the employees of Islami Bank deserve immediate attention to improve customer satisfaction. However, as a result, we have yet to get high awareness and usage of any individual products/services through Islami Bank financing and facilities. Finally, the significant finding is the 'Principle of Religion,' which is the key to selecting a bank's criteria for its customers, where the demographics of clients play a more critical role in determining selection criteria than others.JEL Classification Codes: G01, G21, G24, E58.